The Influence of Organisational Culture on Knowledge Sharing in Selected Municipalities in Limpopo, South Africa - Dikotla, Maoka Andries; Ledwaba, Lethabo (Mousaion: South African Journal of Information Studies, 2023)
Organisational culture is an important factor and has a strong influence on knowledge sharing within institutions. The prevailing culture can either support or compromise knowledge sharing in municipalities. The aim of this study was to investigate the influence of organisational culture on knowledge sharing in some municipalities in Limpopo, South Africa. This study used both quantitative and qualitative research methods. Thus, data was collected using both structured questionnaires and interviews. Quantitative data was analysed using IBM Statistical Package for Social Science (SPSS) 23 software, while qualitative data was analysed using a thematic analysis method. The study revealed that the existing culture in Limpopo municipalities is not conducive to sharing organisational knowledge due to a culture of knowledge hoarding, mistrust, fear and political influence. A policy needs to be developed to protect employees from political influence. To create a conducive environment, where employees can trust each other and knowledge sharing can thrive, managers can encourage staff members to share best practices with their colleagues and consult with them when faced with problems or challenges, rather than taking the challenge to a manager. Municipalities should also build formal recognition and reward systems to compensate employees demonstrating knowledge-sharing behaviours. A comparative study on knowledge sharing in both municipalities and government departments in Limpopo as a whole is recommended.